2003
DOI: 10.1055/s-2003-38498
|View full text |Cite
|
Sign up to set email alerts
|

Ergebnisse einer ambulanten Behandlung von Kindern und Jugendlichen mit Adipositas

Abstract: Treatment programs for obese children and adolescents have to focus on the specific living conditions and eating behaviours of the family especially on age, capacity for self control of the child and the eating behaviour of the father. Local networks to be established within the country for treating obese children coordinated by the paediatrician seem to be best possibilities to provide individual support. In this local networks the prevention of extreme eight increases must be a predominant task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…The majority of the children in the treatment program lost weight and reduced their caloric intakes. Similar to our study, Levine et al [27], Weyhreter et al [35], and Nemet et al [30] also reported that there were significant BMI and BMI SDS reductions as a result of short-term family-based group intervention in obese children.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The majority of the children in the treatment program lost weight and reduced their caloric intakes. Similar to our study, Levine et al [27], Weyhreter et al [35], and Nemet et al [30] also reported that there were significant BMI and BMI SDS reductions as a result of short-term family-based group intervention in obese children.…”
Section: Discussionsupporting
confidence: 90%
“…Compliance with childhood obesity management is generally poor [14] in both family-based group and individual treatment studies, approximately one third of the participants dropped out from the study [13,27,35]. In our study only 5% of the participants did not complete the intervention.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…So konnten verschiedene Studien zeigen, dass unter anderem eine höhere familiäre Belas− tung mit Adipositas mit einer größeren Wahrscheinlichkeit der Persistenz einer kindlichen Adipositas bis ins Erwachsenenalter assoziiert ist [17,18]. In einer anderen Studie fanden die Autoren [19], dass das Gewicht des Vaters negativ mit der Gewichtsver− änderung zum Katamnesezeitpunkt (etwa 2,5 Jahre nach Inter− vention) assoziiert war. Es ist somit nicht auszuschließen, dass Kinder mit adipösen Eltern therapieresistenter sind.…”
unclassified
“…Adipositas hat bereits im Kindesalter vielfältige Auswirkungen auf die Gesundheit, die psychosoziale Entwicklung und die soziale Integration eines Kindes [23,26]. So zeigen rund ein Drittel der adipösen Kinder eine milde Hypertonie und ein Viertel eine Hypercholesterinämie [14], mehr als 2% der adipösen Jugendlichen entwickeln bis zum 30.…”
unclassified